Do higher corporate taxes reduce wages? Micro evidence from Germany - Clemens Fuest; Andreas Peichl; Sebastian Siegloch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
This paper estimates the incidence of corporate taxes on wages using a 20-year panel of German municipalities. Administrative linked employer-employee data allows estimating heterogeneous worker and firm effects. We set up a general theoretical framework showing that corporate taxes can have a negative effect on wages in various labor market models. Using an event study design, we test the predictions of the theory. Our results indicate that workers bear about 40% of the total tax burden. Empirically, we confirm the importance of both labor market institutions and profit shifting possibilities for the incidence of corporate taxes on wages.
Additional information: This paper is a completely revised version of ZEW Discussion Paper No. 13-039.; Older version: http://hdl.handle.net/10419/76727
Keywords: H2; H7; J3; 330; business tax; wage incidence; administrative data; local taxation